2022
DOI: 10.1007/s12369-022-00911-z
|View full text |Cite
|
Sign up to set email alerts
|

Politeness in Human–Robot Interaction: A Multi-Experiment Study with Non-Humanoid Robots

Abstract: We studied politeness in human–robot interaction based on Lakoff’s politeness theory. In a series of eight studies, we manipulated three different levels of politeness of non-humanoid robots and evaluated their effects. A table-setting task was developed for two different types of robots (a robotic manipulator and a mobile robot). The studies included two different populations (old and young adults) and were conducted in two conditions (video and live). Results revealed that polite robot behavior positively af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
0
13
2
1
Order By: Relevance
“…Moreover, exposure to robots is sometimes done with images or videos, rather than in vivo exposure. Yet, the physical presence of a robot (NURSEBOT) increases the tendency for anthropomorphism more than a projection of a robot on a screen [74] and is considered more trustworthy [94]. Another study states that a physically embodied robot (AIBO) is evaluated more positively when participants can touch the robot.…”
Section: General Methodological Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, exposure to robots is sometimes done with images or videos, rather than in vivo exposure. Yet, the physical presence of a robot (NURSEBOT) increases the tendency for anthropomorphism more than a projection of a robot on a screen [74] and is considered more trustworthy [94]. Another study states that a physically embodied robot (AIBO) is evaluated more positively when participants can touch the robot.…”
Section: General Methodological Limitationsmentioning
confidence: 99%
“…The robot's verbal behaviors are of key importance in the interaction (especially when the robot shows collaborative behavior in the conversation with the user). Individuals feel more satisfaction and trust toward a robot with polite behavior [94], and a friendly robot is more appreciated than a robot with unfriendly behavior [36]. The level of interactivity in the conversation is a relevant factor: A robot with highly interactive behavior (enabling sophisticated communication with the participant) is judged more sociable and competent than a robot with lesser communication skills [90].…”
Section: Behavior Is a Crucial Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Однако более молодые совершеннолетние участники исследования меньше доверяли вежливости роботов, чем остальные взрослые. Доверие от взаимодействия с роботом были выше, если общение происходило в очных условиях, и больше симпатии выказывалось мобильному роботу, чем роботу-манипулятору [12].…”
Section: литературный обзорunclassified
“…Previous research on politeness in HRI has produced seemingly contradicting findings regarding this topic. On the one hand, studies focusing on users' perception of polite machines found mostly positive effects of politeness use by agents, for example, increasing the likability of a robot [24], the trust towards non-humanoid robots [12] and the persuasiveness of a virtual agents [11]. On the other hand, studies focusing on the expectations regarding an agents' use of politeness found that users might prefer that robots use more direct language [20] and that indirect or vague language can lead to a bad user experience [7].…”
mentioning
confidence: 99%